Discovery of Multi‐Targets Neuraminidase Inhibitor Lead Compound Against Influenza H1N1 Virus A/WSN/33 Based on QSAR, Docking, Dynamics Simulation and Network Pharmacology. Issue 14 (7th April 2022) - Sun, Jiaying; Liu, Yaru; Yi, Bingxiang; Shu, Mao; Zhang, Zhiping; Lin, Zhihua
Abstract: In this paper, three compounds are discovered as lead compounds of multi‐targets neuraminidase inhibitor drugs against influenza H1N1 virus A/WSN/33 using QSAR, molecular docking, dynamics simulation and network pharmacology. Moreover, NEU1, PLA2G1B and STAT1 are especially related to therapeutic targets of influenza virus. Therefore, the present study can be helpful in the process of the rational drug design of anti‐influenza virus drugs and improve reliability of findings novel multi‐target drugs which may avoid drug‐resistance. Abstract : To find novel multi‐target neuraminidase inhibitor (NIs) drugs and avoid drug‐resistance, this study comprehensively utilized QSAR (quantitative structure‐activity relationship), molecular dynamics simulation, molecular docking and network pharmacology methods and perform virtual screen. Finally, three compounds are discovered as lead compounds of multi‐targets NIs drugs against influenza H1 N1 virus A/WSN/33. Moreover, NEU1, PLA2G1B and STAT1 are recommended as especially related therapeutic targets of influenza virus.